2009
DOI: 10.1136/ard.2008.105296
|View full text |Cite
|
Sign up to set email alerts
|

ARTS1 polymorphisms are associated with ankylosing spondylitis in Koreans

Abstract: This is first confirmation in a non-Caucasian population that genetic polymorphisms in ARTS1 are associated with AS, implicating common pathogenetic mechanisms in Korean and Caucasian patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 16 publications
5
47
0
3
Order By: Relevance
“…The Wellcome Trust CaseControl consortium and Australo-Anglo-American Spondyloarthritis Consortium first described the association of five ERAP1 single nucleotide polymorphisms (SNPs) and AS (Consortium WTCCC/TASC, 2007), namely rs27044, rs17482078, rs10050860, rs30187 and rs2287987. Two of these SNPs, rs27044 and rs30187, gathered more consistent results in the subsequent reports and were the only markers that showed significant association both in Caucasian and in Han Chinese groups (Choi, et al, 2010;Harvey, et al, 2009a;Maksymowych, W. P., et al, 2009;Pazar, et al, 2010;Pimentel-Santos, et al, 2009). The significant relation between rs27044 and AS was not confirmed in Canadian, contrarily to all other replicates involving this SNP and Caucasian groups.…”
Section: Erap1/arts1supporting
confidence: 50%
See 1 more Smart Citation
“…The Wellcome Trust CaseControl consortium and Australo-Anglo-American Spondyloarthritis Consortium first described the association of five ERAP1 single nucleotide polymorphisms (SNPs) and AS (Consortium WTCCC/TASC, 2007), namely rs27044, rs17482078, rs10050860, rs30187 and rs2287987. Two of these SNPs, rs27044 and rs30187, gathered more consistent results in the subsequent reports and were the only markers that showed significant association both in Caucasian and in Han Chinese groups (Choi, et al, 2010;Harvey, et al, 2009a;Maksymowych, W. P., et al, 2009;Pazar, et al, 2010;Pimentel-Santos, et al, 2009). The significant relation between rs27044 and AS was not confirmed in Canadian, contrarily to all other replicates involving this SNP and Caucasian groups.…”
Section: Erap1/arts1supporting
confidence: 50%
“…Since the confirmed association between ERAP1 and AS reported in 2007 (Consortium WTCCC/TASC, 2007), some replications occurred in studies involving Caucasian (Consortium TASC, 2010;Harvey, et al, 2009a;Maksymowych, W. P., et al, 2009;Pazar, et al, 2010;Pimentel-Santos, et al, 2009;Tsui, F. W., et al, 2010) and Han Chinese cohorts (Bang, et al, 2011;Choi, et al, 2010;Davidson, et al, 2009). The Wellcome Trust CaseControl consortium and Australo-Anglo-American Spondyloarthritis Consortium first described the association of five ERAP1 single nucleotide polymorphisms (SNPs) and AS (Consortium WTCCC/TASC, 2007), namely rs27044, rs17482078, rs10050860, rs30187 and rs2287987.…”
Section: Erap1/arts1mentioning
confidence: 99%
“…A literature search in the PubMed database resulted in the identification of 22 studies; 12 studies met the study inclusion criteria, including four studies from European populations and eight studies from Asian populations (two from Korean, six from Chinese populations), including the present study 9, 25, 26, 30, 31, 34, 35, 37, 38, 39, 40. Ten studies were excluded (seven studies due to lack of data and three studies having duplicate data).…”
Section: Resultsmentioning
confidence: 99%
“…The SNPs rs27037, rs27980 and rs27582 were reported to be in strong linkage disequilibrium (LD), as well as the SNPs rs30187 and rs27434 and the SNPs rs2549782 and rs2248374. Based on conflicting results in several studies 9, 10, 24, 25, 26, all sites were selected for the current study (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, studies have identified the combination of the major allele of rs30187 (coding for R528) and the minor allele at rs10050860 (coding for N575) being protective against AS (a fourfold reduction in AS risk) (2). In addition, haplotypes K528/D575/R725, K528/D575/E730, R528/D575/R725/E730, and K528/D575/R725/Q730 have been shown to be associated with AS (10)(11)(12). The in vitro assessment of single amino acid ERAP1 variants corresponding to the AS-associated SNPs revealed reduced trimming activity for R528, Q725, and E730 but not N575 (2,13,14).…”
mentioning
confidence: 99%